Monitoring and Analysis of Induction Motor Behavior Using Haiwell Cloud SCADA with Tension Control Method - Hanif Rifai Adha; Daeng Rahmatullah; Danang Arengga W (INAJEEE (Indonesian Journal of Electrical and Electronics Engineering), 2026)
In the modern industrial sector, monitoring the condition of induction motors is the main key to maintaining efficiency and reliability. Internet of Things (IoT) technology in the monitoring system can be done in real-time, to provide convenience in monitoring induction performance. Haiwell Cloud SCADA-based monitoring system to analyze the behavior of induction motors in real-time voltage, current, speed, frequency, and temperature. This system integrates a tension control method using a magnetic powder brake to simulate changes in the load dynamically. The results show that at a low torque of 0 – 6 Nm, the induction motor operates stably at a speed close to synchronous with a low stator current. However, at torques above 8 Nm, there is a significant voltage drop, and the stator current increases four times compared to the nominal current, and there is a temperature increase of up to 35oC, which represents an increase in power losses. This research offers a combination of IoT-based monitoring and tension control methods. IoT-based monitoring systems help users easily monitor the performance of induction motors in real-time and anticipate potential problems before failures occur.